FLASH proton irradiation setup with a modulator wheel for a single mouse eye. Issue 4 (1st March 2021) - Kourkafas, Georgios; Bundesmann, Juergen; Fanselow, Timo; Denker, Andrea; Ehrhardt, Vincent Henrique; Gollrad, Johannes; Budach, Volker; Weber, Andreas; Kociok, Norbert; Joussen, Antonia M.; Heufelder, Jens
Abstract : Purpose: Recent studies indicate that FLASH irradiation, which involves ultra‐high dose rates in a short time window (usually >40 Gy/s in <500 ms), might be equally efficient against tumors but less harmful to healthy tissues, compared to conventional irradiation with the same total dose. Aiming to verify the latter claim for ocular proton radiotherapy, in vivo experiments with mice are being carried out by Charité – Universitätsmedizin Berlin. This work presents the implemented setup for delivering FLASH proton radiation to a single eye of mice at the Helmholtz‐Zentrum Berlin für Materialien und Energie (HZB). Materials and methods: The HZB cyclotron is tuned to provide a high‐intensity 68 MeV focused proton beam. Outside the vacuum beamline, the protons hit a single scatterer, which also serves as range shifter, and a rotating modulator wheel, which produces a flat depth‐dose distribution. Two transmission ionization chambers in between, read out by fast electronics, are used as dose monitors for triggering an in‐vacuum beam shutter, which blocks the beam once the desired dose has been delivered. A collimating aperture shapes the radiation field at the isocenter, which is measured by a radioluminescent screen and a CCD camera. At the same position, a parallel‐plate ionization chamber of type Advanced Markus ® is used for absolute dosimetry and characterization of the spread‐out Bragg peak inside a water phantom. A thin‐foil mirror of adjustable tilt in the beam path assists the correct alignment of the target through side illumination. Radiochromic films of type EBT3 are used to supplement the dosimetry and assist the alignment. Results: A dose rate of 75 Gy/s has been measured, delivering within 200 ms 15 Gy (RBE) with a reproducibility better than ±1%. A depth‐dose curve with a range of 5.2 mm in water, 0.9 mm distal fall‐off (90%–10%), and ±2.5% ripple has been demonstrated, with a PTV of 6.3 mm diameter, 1.7 mm lateral penumbra (90%–10%), 8% uniformity, and 3% symmetry. Conclusions: The implemented setup is able to accommodate ocular irradiation of narcotized mice with protons, targeting selectively the left or the right eye, under conventional and FLASH conditions. Switching between these two modes can be done within half an hour, including the calibration of the dose monitors and the verification of the dose delivery. Further upgrades are planned after the completion of the on‐going experiment. Abstract :